Financial system, and SME financing in Kazakhstan - Yergali Dosmagambet; Yessengali Oskenbayev; Farhad Taghizadeh-Hesary; Moldir Mukan (Asian Development Bank Institute (ADBI), 2018)
Kazakhstan remains a resource-dependent country, and the overall economy experiences external commodity price volatility. Oil export revenue exerts a positive effect on the economic development of oil-producing countries; however, depending only on oil revenue will make the economy vulnerable to oil price shocks, especially in the case of an oil price recession. This is forcing the Kazakhstan Government to pursue industrial diversification to accomplish sustainable and balanced economic development, particularly concentrating on the diversification and expansion of the SME sector. Second-tier banks remain SMEs' main source of financing. Due to the higher risks associated with SMEs, they have to borrow money at high interest rates that endanger their growth. Since the global crisis in 2008 and the adoption of the Basel capital requirement, banks have become more reluctant to lend funds to SMEs. The government's use of a credit guarantee scheme (CGS) relies on the willingness of second-tier banks to lend to SMEs, since they decide which SMEs to lend to and the effective interest rate. Second-tier banks, on the other hand, are dependent on the oil price volatility. This paper examines the status of the CGS in SME financing in Kazakhstan. In addition, it provides an empirical analysis using the structural VAR method that shows that the creditworthiness of the whole financial system in Kazakhstan is dependent on oil prices. Moreover, there is an effect from oil price volatility on currency value change, which also influences the financial situation of SMEs.
Keywords: G01; G32; Q31; 330; small and medium-sized enterprises; SMEs; credit guarantee scheme; oil price; Kazakhstan